2011
DOI: 10.3390/e13091541
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Controlled Atom-Photon Entanglement in a Three-Level V-Type Atomic System via Spontaneously Generated Coherence

Abstract: Abstract:We investigate the dynamical behavior of the atom-photon entanglement in a V-type three-level quantum system using the atomic reduced entropy. It is shown that an atom and photons are entangled at the steady-state; however disentanglement can also be achieved in an special condition. It is demonstrated that in the presence of quantum interference induced by spontaneous emission, the reduced entropy and the atom-photon entanglement are phase-dependent. A non-stationary solution is also obtained when th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…While considering the SGC effect, we apply the EIT effect to the research on the entorpy of entanglement. Due to the presence of the incoherent pump, even though the probe is very weak, we are surprised to find that the SGC effect can influence the DEM [39][40][41][42][43][44] conditionally. Moreover, by comparing with the gain or absorption of the atom system in both steady Figure 1.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…While considering the SGC effect, we apply the EIT effect to the research on the entorpy of entanglement. Due to the presence of the incoherent pump, even though the probe is very weak, we are surprised to find that the SGC effect can influence the DEM [39][40][41][42][43][44] conditionally. Moreover, by comparing with the gain or absorption of the atom system in both steady Figure 1.…”
Section: Introductionmentioning
confidence: 87%
“…Generally, narrowing down the decay rate is expected. However, a previous work demonstrated that the SGC effect between two spontaneous emissions in the V-type system has a major role in establishing the atom-photon entanglement [39]. It is found that in the presence of SGC effect, the reduced entropy and the atom-photon entanglement are phase-dependent.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations